Analgesic efficacy of ultrasound-guided transversus abdominis plane block in dogs undergoing ovariectomy - Cavaco, Jéssica Sperandio; Otero, Pablo Ezequiel; Ambrósio, Aline Magalhães; Neves, Ieda Cristina Boni; Perencin, Felipe Montanheiro; Pereira, Marco Aurélio Amador; Matera, Julia Maria; Fantoni, Denise Tabacchi (Frontiers in Veterinary Science, 2022)
Background: In medicine, the transversus abdominis plane (TAP) block has been shown as an effective method of analgesia in several surgical procedures. In this context, this prospective, randomized, blinded study aimed to evaluate the analgesic efficacy of TAP block, guided by ultrasound in female dogs submitted to ovariectomy. Methods: Therefore, 32 animals randomly assigned in two groups (n = 16) were used. Groups consisted of TAP block control (TBC) which received water injection (0.2 mL kg-1 point), and TAP block bupivacaine (TBB) which received bupivacaine (0.2 mL kg-1 point at 0.25%); 25 both groups were submitted to four-point approach. Animals were premedicated with acepromazine (0.03 mg kg-1) and meperidine (2 mg kg-1) IM, propofol was used as anesthetic induction (3 to 5 mg kg-1) IV, and isoflurane was used to maintain. To standardize groups, the animals received a continuous infusion of remifentanil (0.2µg kg-1 min) and rocuronium (0.6 mg kg-1) IV in the intraoperative period. Variables measured were the heart and respiratory rates, blood pressure, temperature, peripheral oxyhemoglobin saturation, exhaled carbon dioxide concentration, exhaled isoflurane concentration, serum cortisol, analgesia, and sedation. Before the preanesthetic medication (Baseline) and 1, 2, 4, 6, and 8 hours after extubation, pain and sedation were assessed using a numeric rating scale (NRS), Glasgow composite measure pain scale (GCMPS-SF), and sedation scale. Moreover, serum cortisol was measured at different moments. Results: the results show that in the intraoperative period, there was no significant difference between groups. After surgery, in TBC, 13 out of 16 animals required analgesic rescue, whereas, in TBB, this occurred only in one animal. Regarding the measurement of serum cortisol, the TBC group showed a significant difference when compared to the baseline time in the traction of the first ovary (P<0.0001), 2 hours (P=0.0441), and 8 hours (P=0.0384) after extubation. In TBB, cortisol showed a significant increase only in the traction of the first ovary and 2 hours after extubation (P<0.0001). Conclusion: The technique using ultrasound-guided TAP block in two points approach by hemiabdomen with 0.2 mL kg-1 bupivacaine 0.25% was effective in providing postoperative analgesia in dogs undergoing ovariectomy.